Physicochemical properties, bioactive compounds degradation kinetics, and microbiological counts of fortified pomegranate gummy candy (GC) during ambient storage - Qi, Ng An; Noor Hasnan, Noor Zafira; Kadir Basha, Roseliza; Alyas, Nur Diyana; Mohd Zulkifli, Nurin Izzati (Universitas Brawijaya, 2023)
This study explored the potential of fortified pomegranate gummy candies (GC) as a solution for insufficient vitamin C and phenol intake. It entailed two objectives: assessing the impact of ambient storage (20±2 ℃) on various GC properties and developing kinetic models to predict vitamin C and phenol degradation during storage. The study involved the preparation of GC using a modified formulation and examined moisture content, water activity, texture, vitamin C, total phenolic content, and microbiological counts during 15-day-storage. Findings revealed that the moisture content decreased from 21.82% to 13.41%, potentially affecting texture. Water activity remained high (0.84-0.86), posing potential microbiological risks. The textural analysis indicated high hardness, springiness, gumminess, and chewiness, which may impact consumer acceptance. Adhesiveness remained minimal. Vitamin C decreased from 2,176.90 mg AA/100g to 1,419.10 mg AA/100g, possibly influenced by moisture and oxygen. Phenolic content decreased from 2,845.97 mg GAE/100g to 2,183.70 mg GAE/100g, remaining remarkably high. Kinetic modeling revealed that zero-order kinetics best described degradation, with constant degradation rates. In conclusion, fortified pomegranate GC demonstrate potential as functional food. However, further research is necessary to optimize texture properties, improve formulation and understand complex interactions between gelatin and phenolic compounds for enhanced consumer acceptance and health benefits.